CD4 + T cells drive corneal nerve damage but not epitheliopathy in an acute aqueous-deficient dry eye model - Vereertbrugghen, Alexia (2024)
Dry eye disease (DED) is characterized by a dysfunctional tear film in which the corneal epithelium and its abundant nerves are affected by ocular desiccation and inflammation. Although adaptive immunity and specifically CD4+ T cells play a role in DED pathogenesis, the exact contribution of these cells to corneal epithelial and neural damage remains undetermined. To address this, we explored the progression of a surgical DED model in wild-type (WT) and T cell-deficient mice. We observed that adaptive immune-deficient mice developed all aspects of DED comparably to WT mice except for the absence of functional and morphological corneal nerve changes, nerve damage-associated transcriptomic signature in the trigeminal ganglia, and sustained tear cytokine levels. Adoptive transfer of CD4+ T cells from WT DED mice to T cell-deficient mice reproduced corneal nerve damage but not epitheliopathy. Conversely, T cell-deficient mice reconstituted solely with naïve CD4+ T cells developed corneal nerve impairment and epitheliopathy upon DED induction, thus replicating the WT DED phenotype. Collectively, our data show that while corneal neuropathy is driven by CD4+ T cells in DED, corneal epithelial damage develops independently of the adaptive immune response. These findings have implications for T cell-targeting therapies currently in use for DED.